Privileges Fund Management Based on Performance-Based Budgeting Principles - Ariyanti Luhur Tri Setyarini; Riawan Tjandra; Vicki Dwi Purnomo (International Journal of Scientific Multidisciplinary Research, 2023)
Based on Law Number 13 of 2012 concerning the Privileges of the Special Region of Yogyakarta, it is regulated based on regional government laws. The government provides funding known as the Privileges Fund. This Privileges Fund is managed must realize the principles of good governance, to achieve the goal of privilege in particular, and the goal of the state to prosper society in general. This study uses an empirical juridical method using a statutory approach and a conceptual approach. This study aims to find out how the management of performance-based privilege funds is implemented